2023
DOI: 10.1002/smll.202206709
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Stimuli‐Response Polychromatic Carbon Dots for Advanced Information Encryption and Safety

Abstract: the requirements of the market because counterfeiters have very sophisticated techniques to replicate current anticounterfeiting techniques. [2] Thereby, the development of advanced information encryption and anti-counterfeiting strategies that are difficult to replicate is of great significance and has an irreplaceable position in practical application. Based on this background, stimuli-response information encryption and anti-counterfeiting techniques are proposed to achieve high information encryption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 194 publications
0
26
0
Order By: Relevance
“…Therefore, it is crucial to develop new strategies and systems for multidimensional information encryption with diverse input/output in one material system, as this approach offers superior resistance to forgery and a high capacity for information storage. [10][11][12][13] Perylene bisimides (PBI), a star class of π-conjugated chromophores, have gained significant attention in the fields of dyes and pigments due to their unique photophysical properties, strong electron affinity, tunable self-assembly behavior, and ease of functionalization. [14][15][16] Especially, the electron-withdrawing character endows PBI with the ability to be reduced to radical anions PBI *À and dianions PBI 2À , exhibiting distinct color changes with red-shift absorption towards the near-infrared region.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial to develop new strategies and systems for multidimensional information encryption with diverse input/output in one material system, as this approach offers superior resistance to forgery and a high capacity for information storage. [10][11][12][13] Perylene bisimides (PBI), a star class of π-conjugated chromophores, have gained significant attention in the fields of dyes and pigments due to their unique photophysical properties, strong electron affinity, tunable self-assembly behavior, and ease of functionalization. [14][15][16] Especially, the electron-withdrawing character endows PBI with the ability to be reduced to radical anions PBI *À and dianions PBI 2À , exhibiting distinct color changes with red-shift absorption towards the near-infrared region.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots (CDs), a new class of RTP material, have become more attractive among the conventional RTP materials due to their abundant raw materials, mild preparation methods, high quantum efficiency, good water solubility, ignorable toxicity, and high photobleaching resistance. CDs hold great potential in anti-counterfeiting, 12,13 light-emitting diodes, 14 biochemical sensors 15 and other diverse fields. However, previous research studies have demonstrated that multiple functional groups on the surface of CDs make them unstable, reacting with oxygen and water easily under ambient conditions, and therefore the luminescence of CDs is easily quenched.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, developing fascinating CDs with versatile properties has received great attention in many fields. [7][8][9][10][11] The most predominant characteristic of CDs is that they have remarkable properties, such as tunable photoluminescence, 12 high fluorescence quantum yield (QY), 13,14 ease of surface functionalization, 15 good aqueous solubility, 16 superior biocompatibility, 17 and high photostability, 18,19 have received immense research attention, which enables CDs to be an excellent alternative to semiconductor quantum dots (QD) with a wide variety of promising applications in the fields of sensing, 20 bioimaging, 21 biomedicine, 22 electronic devices, 23 and anti-counterfeiting. 24 In the initial development stage of CDs, the main research focuses on the preparation of carbon dots, utilizing a large number of carbon sources and numerous approaches.…”
Section: Introductionmentioning
confidence: 99%